EFEKTIFITAS MANAJEMEN KELAS DALAM MENINGKATKAN PRESTASI BELAJAR : Evaluasi Belajar, Prestasi Belajar - reni, dewi susilo (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2023)
Abstract: Effective classroom management plays an important role in improving student achievement in elementary schools. This research aims to evaluate the effectiveness of classroom management in improving learning achievement at SDN Kedunggalar 1. The research method used is a case study involving direct observation, interviews and document analysis. The research results show that the implementation of effective classroom management significantly contributes to increasing student learning achievement. These findings provide important implications for the development of better classroom management strategies to improve the quality of education at the primary level. Keywords: Classroom Management, Learning Achievement, Elementary School